(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the role of recreational geography within the system of geography sciences and the recreational potential of the Republic of Uzbekistan. It also examines the social-political and spiritual-pedagogical factors influencing the development of tourism in Uzbekistan at the new stage of its development, and explores the possibilities for its growth.